Breast cancer screening program attitudes among women from WielkopolskaThe report from Focus Group Interview (FGI) studies - Pietrzak, Paulina; Godlewski, Dariusz; Adamczak, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2011)
Goals : The assessment of breast cancer screening program attitudes among women from Wielkopolska. The research was ordered by the Center of Cancer Prevention and Epidemiology in Poznań. It was conducted between 30. 01. 2009 and 11. 02. 2009. Materials: The research has been conducted in the Breast Cancer Screening Program target group (women between 50 to 69 years old). This program is financed in Poland by Ministry of Health. Participants were divided into six groups of 7-12 women by place of residence and level of education. Methods : The Focus Group Interview was used. The conversations was led by the moderator. The discussion was conducted as informal as it was possible. The main aim of moderator was to encourage women to exchange opinions spontaneously. Conclusions : 1. None of the women had a mammography in last two years. 2. Women do not attend breast cancer screening program because they do not receive invitations. 3. Mammography in mobile mammography units is the best solution for women from villages because they do not have to worry about traveling to the city. 4. Some of the women from families without the history of cancers think that they will never be diagnosed with cancer. 5. The biggest irrational reason for avoiding mammography is the fear of cancer diagnosis. 6. The recent mass media mess about the low quality of mammography is still in women’s memory. 7. Most of the respondents avoid contacts with the health service.